Railways in Brazil: Future and ongoing projects (Research, Society and Development, 2021)
The Brazilian truck drivers' strike in Brazil in May 2018 was merely an illustration of the current scenario of transportation modes in the country. The dominant use of the highways in relation to other modalities means that the logistics and transportation of cargo and passengers throughout the national territory is precarious and deficient. The predominance of the modal route results in underutilization of railways, one of the most important modalities in the development of great world powers, such as Germany and the United States. Thus, this research aims to analyze the current and future scenario of Brazilian railways. For this, future and ongoing projects of this mode of transport in Brazil were researched in the literature. Even nowadays it is very unexplored, the Brazilian railway network has an enormous potential, which, in order to be better utilized, needs to be increased. Making projects that are being built and future projects can expand the country's rail network.